Documenting Myanmar's Social Transformation : Insights from Six Rounds of Research on Livelihoods and Social Change in Rural Communities - Pursch, Samuel (World Bank, Washington, DC, 2017)
This paper presents the initial findings from six rounds of research conducted between 2012 and 2016 on livelihoods and social change in rural Myanmar, undertaken as part of the Qualitative Social and Economic Monitoring initiative. These data provide unique insights into the ways in which broad processes of democratization and globalization -- put into effect following Myanmar's historic reforms beginning in 2011 -- are experienced at the village level. The analysis focuses on three key aspects of the "social contract": local governance mechanisms, shifting expectations of the state, and changes in the types of networks connecting villagers to regional and global markets. Remarkable social progress has been made in Myanmar since 2012, yet there are no grounds for complacency. Managing ongoing transformations in these three domains, in ways perceived to be locally legitimate and effective, will be crucial if the initial gains are to be consolidated and expanded.